Time-dependent changes in the serum levels of prolactin, nesfatin-1 and ghrelin as a marker of epileptic attacks young male patients - Aydin, Suleyman; Dag, Ersel; Ozkan, Yusuf; Arslan, Ozgur; Koc, Guray; Bek, Semai; Catak, Zekiye (Elsevier Science Inc, 2011)
A relationship between hormones and seizures has been reported in animals and humans. Therefore, the purpose of this study was to investigate the association between serum levels of prolactin, nesfatin-1 and ghrelin measured different times after a seizure or non-epileptic event and compared with controls. The study included a total of 70 subjects, and of whom 18 patients had secondary generalized epilepsy (SGE), 16 patients had primary generalized epilepsy (PGE), 16 patients exhibited paroxysmal event (psychogenic) and 20 healthy males were control subjects. The first sample was taken within 5 min of a seizure, with further samples taken after 1, 24, and 48 h so long as the patient did not exhibit further clinically observable seizures; blood samples were taken once from control subjects. Prolactin was measured immediately using TOSOH Bioscience hormone assays. Nesfatin-1 and ghrelin peptides were measured using a commercial immunoassay kit. Patients suffering from focal epilepsy with secondary generalization and primary generalized epilepsy presented with significantly higher levels of serum prolactin and nesfatin-1 and lower ghrelin levels 5 min, 1 and 24 h after a seizure than patients presenting with paroxysmal events (psychogenic) and control subjects; the data were sirnilar but not statistically significant after 48 h. The present study suggests that increased serum prolactin and nesfatin-1 concentrations, decreased ghrelin concentrations could be used as markers to identify patients that have suffered a recent epileptic seizure or other paroxysmal event (psychogenic). (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Prolactin; Nesfatin-1; Ghrelin; Epilepsy